IDENTIFIKASI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN TOBO-TOBO (Ficus septica Burm) TERHADAP BAKTERI ULKUS DIABETIK - Munifah Wahyuddin; Afrisusnawati Rauf; Nurshalati Tahar; Nurfitrah Syamsuddin; Huriyah Fadhilah (CERATA Jurnal Ilmu Farmasi, 2024)
People in Indonesia have long used tobo-tobo leaves (Ficus septica Burm). The ingredients contained in these leaves consist of alkaloid compounds, saponins, flavonoids, and tannins, which are compounds that are antibacterial, so they have the potential to be developed as plants. drug. This study aims to determine the antibacterial activity of the ethanol extract of tobo-tobo leaves against diabetic ulcer bacteria, namely Pseudomonas aeruginosa, Providencia stuartii, Citrobacter freundii, Pseudomonas luteola, Burkholderia cepacia, Acinetobacter baumannii, and Proteus merabilis. For this kind of research, a quantitative experimental method is used. The ethanol solvent is used for extraction, and the agar diffusion method on NA medium is used to test for bacteria. The test showed that the tobo-tobo (Ficus septica Burm) leaf extract made of ethanol had alkaloids, saponins, flavonoids, and tannins in it. In the antibacterial activity test on each extract with a concentration of 20%, 40%, 60%, 80%, and 100%, it was found that the ethanol extract of tobo-tobo leaves at a concentration of 100% gave the greatest antibacterial effect on bacterial growth with an average diameter value of flat. average: Pseudomonas aeruginosa 12.8 mm (strong), Providencia stuartii 9.33 mm (medium), Citrobacter freundii 11.83 mm (strong), Pseudomonas luteola 11 mm (strong), Burkholderia cepacian 10.16 mm (strong), Acinetobacter baumannii 9.5 mm (moderate), and Proteus merabilis 6.5 mm (moderate).